Homology Modelling and Insilico Analysis of Matrix Protein M1 In H1N1 Influenza a Virus - Abhilash. M (International Journal of Pharma and Bio Sciences, 2010)
World wide spread of H1NI Influenza A Virus has raised concerns. Modelling of Matrix protein m1 of Influenza A virus protein was done using Modeller 9V2. Modelled structure was submitted to protein model database and can be downloaded using accession number . Further modelled protein structure was subjected to Insilco analysis using various Bioinformatics tools. Two anti-influenza drugs currently being used to treat infected patients are oseltamivir (Tamiflu) and zanamivir (Relenza), both of which target the neuraminidase enzyme of the virus. Reports of the emergence of drug resistance make the development of new anti-influenza molecules a priority. Hence, modelled structure of H1NI Matrix m1 will be very useful for insilico analysis of potential Matrix protein m1 inhibitors.